Transmission of the gut microbiome in cohousing goats and pigs - Zhang, Tingting; Li, Mao; Shi, Tao; Yan, Yueyang; Niyazbekova, Zhannur; Wang, Xihong; Li, Zongjun; Jiang, Yu (Frontiers in Microbiology, 2022)
Social interaction facilitates the horizontal transmission of the microbiota between different individuals. However, little is known about the level of microbiota transmission in different livestock animals and different digestive tracts. The Hainan black goat and Wuzhishan pig are typical tropical local breeds in Hainan Island in China. Thus, we sampled and analyzed the gut microbiome in Hainan black goats (cecum and rumen) and Wuzhishan pigs (cecum) to study horizontal transmission by rearing them in same pen (6 goats and 6 pigs) or separate pens (9 goats and 9 pigs). De novo assembly and binning recovered 3,262 strain-level and 2,488 species-level metagenome-assembled genomes (MAGs) using ~1.3 Tb sequencing data, identifying 1,865 novel MAGs at strain-level. Results showed that social interaction promotes homogeneity in the gut community memberships of the different goat rumen (P < 0.05), goat cecum (P < 0.05), and pig cecum. Notably, approximately 7.08% (231/3262) of the gut microbial population could transmit during the cohousing, 12 strains only in the inter-species transmission, versus 190 strains only in intra-species transmission, and 10 strains only in foregut and hindgut transmission. However, we were unable to determine the direction of transmission nor whether it was direct. In addition, the social contact group has high transmitted strain abundance, which is correlated with community composition. Our study provided new insight into the influence of social interaction on the animal gut microbiota.